Rapporter - Hodkinson, Juliana; Marstal, Henrik; Mølle, Thorkil; Barnholdt Hansen, Jette; Holt, Fabian; Michelsen, Morten; Petersen, Nils Holger; Schwab, Heinrich W.; Fessel, Hjarne; Holme Hansen, Thomas; et al. (Danish Yearbook of Musicology, 2004)
Research Projects Silences in 20th- and 21st-century music and sound-art (Juliana Hodkinson) Dansk rock mellem tradition og modernitet (Henrik Marstal) Grundstrukturer i den polyfone sats ca. 1350-1600 (Thorkil Mølle) Ars rhetorica og .stetikken (Jette Barnholdt Hansen) Genre Cultures in Popular Music (Fabian Holt) Dansk rockkultur fra 50’erne til 80’erne (Morten Michelsen) The Cultural Heritage of Medieval Rituals (Nils Holger Petersen & Heinrich W. Schwab) Conferences Musik og Intermedialitet (Hjarne Fessel) Medieval and Renaissance Music Conference, Jena 2003 (Thomas Holme Hansen) Svenska samfundet för musikforsknings 5. konference, Göteborg 2003 (Bo Marschner) Third Biennial International Conference on Twentieth-Century Music, Nottingham 2003 (Steen Kaargaard Nielsen) Danish Musicological Society, 2003 (Morten Michelsen)